Experimental study of the effect of filler on the ductility of filler-bitumen mastics. (20th November 2018) - Pereira, L.; Freire, A.C.; Sá da Costa, M.; Antunes, V.; Quaresma, L.; Micaelo, R.
Highlights: The force-ductility curve is a function of the normalized filler concentration value. The normalized post-peak deformation energy is proposed for the ductility test analysis. Normalized filler concentration values close to 0.80 induce a clear reduction in ductility. Waste materials showed a similar effect on the ductility of filler-bitumen mastics. Abstract: This research investigated the effect of filler on the ductility of filler-bitumen mastics, as a surrogate of the cohesive behaviour and the tensile properties. Various fillers (industrial products, mineral fillers or waste materials) were mixed with one paving grade bitumen, in various filler-to-bitumen ratios, and tested under the force-ductility test. The force-elongation curve obtained is affected by the constituents, but the peak force and total deformation energy are a mainly a function of the normalized filler concentration value. Moreover, the effect of the filler type and concentration on the specimen's ductility is better perceived from the normalized post-peak deformation energy. Normalized filler concentration values close to 0.80 induce a clear reduction in ductility.